Truth machine : the contentious history of DNA fingerprinting - Lynch, Michael, 1948- (University of Chicago Press, 2008)
DNA profiling-commonly known as DNA fingerprinting-is often heralded as unassailable criminal evidence, a veritable "truth machine" that can overturn convictions based on eyewitness testimony, confessions, and other forms of forensic evidence. But DNA evidence is far from infallible. It is subject to the same possibilities for error-in sample collection, forensic analysis, and clerical record keeping-as any other aspect of criminal justice practice. Truth Machine traces the controversial history of DNA fingerprinting by looking at court cases in the United States and United Kingdom beginning in the mid-1980s, when the practice was invented, and continuing until the present. Using interviews, observations of courtroom trials and laboratory processes, and documentary reconstruction, the authors provide a nuanced, theoretically sophisticated, and original ethnographic account of DNA fingerprinting and its evolution. Ultimately, Truth Machine presents compelling evidence of the obstacles and opportunities at the intersection of science, technology, sociology, and law.--From publisher information.